Human Papillomavirus: Mini-review and Collateral Expected Benefits of the Vaccine - Zeron, Hugo Mendieta; Lopez, H; Layton, T; Santillan, B; Colin, F; Camarillo, R; Dominguez, G (Nepal Journal of Obstetrics and Gynaecology, 2013)
Cervical neoplasia is the second leading cause of neoplastic death in Latin America. It is generally accepted that all cervical carcinomas have at least one high risk Human Papillomavirus (HPV). Due to the causal relationship of specific HPV types and cervical cancer and its role as precursor of skin lesions it is important to identify the involved genotype. HPV, as other tumor-viruses, induces oncogenesis by manipulating an array of different cellular pathways, which leads to immortalization and proliferation of the infected cells by disrupting the mitotic checkpoint upon infection of the host cell. Actually the role of the immune response in the development of cervical cancer is unknown as is the relationship between the type and level of expression of messenger RNA (mRNA) of interferon gamma (IFN-γ), transforming growth factor beta 1 (TGF-β1) and interleukin (IL)-4 in the cervical microenvironment within each of the stages of carcinogenesis with the HPV genotype causing the infection. An average annual cost to treat cervical cancer is U.S. 10,283 per patient. Taking into account the World Population Prospects: The 2010 Revision, in ten years the accumulated cases of cervical cancer might be 3,286,534, thus making a total budget of U.S. 33,795.4 million to treat all women. Universal vaccination against HPV might result in extended benefits as the decrease in mouth and oropharynx cancers as well as the reduction in health cost for the attendance of several neoplasias. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 4-9 DOI: http://dx.doi.org/10.3126/njog.v8i1.8852